1995
DOI: 10.1155/tsm.23.61
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Initial Grain Size on the Rolling and Recrystallization Textures in the Alloy Al‐1.8% Cu

Abstract: The influence of the initial grain size prior to deformation on the rolling and recrystallization textures is investigated in the alloy Al-l.8wt%Cu by X-ray macrotexture analysis. Two different particle stages are examined: (i) Small shearable precipitates give rise to shear band formation and, during annealing, to nucleation of recrystallization at shear bands. (ii) Large particles cause particle stimulated nucleation of recrystallization (PSN). The microstructural evolution, particularly during recrystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Since SBs largely affect the stored energy distribution, they may have a strong impact on the recrystallization behavior, and in many cases SBs act as preferred nucleation sites [14][15][16][17][18]. Ample evidence exists that preferred nucleation of certain orientations occurs at SBs [14,16,19]. In the present case, this was verified by analyzing the EBSD scans collected on the cryogenically rolled sample.…”
Section: Deformed State After 75% Deformationsupporting
confidence: 57%
See 2 more Smart Citations
“…Since SBs largely affect the stored energy distribution, they may have a strong impact on the recrystallization behavior, and in many cases SBs act as preferred nucleation sites [14][15][16][17][18]. Ample evidence exists that preferred nucleation of certain orientations occurs at SBs [14,16,19]. In the present case, this was verified by analyzing the EBSD scans collected on the cryogenically rolled sample.…”
Section: Deformed State After 75% Deformationsupporting
confidence: 57%
“…7b and 8). The orientations that are associated with nucleation at SBs in Al-alloys, namely Q, Goss, R (retained rolling) and ND rotated cube [14,16,[19][20][21] are also observed in the SBs of the 75% cryogenically deformed pure copper. The Goss and the Q components are thought to result from positive and negative TD rotations associated with the formation of SBs in copper {1 1 2}h1 1 1i and S {1 2 3}h6 3 4i oriented grains [22,23].…”
Section: Effect Of Rt and Cryogenic Rolling On The Deformation Microsmentioning
confidence: 82%
See 1 more Smart Citation
“…The strong impact of the initial texture on rolling texture may overshadow the influence of other material parameters. It has been shown that a decrease in initial grain size leads to an accelerated rate of rolling texture evolution [10,11]. Deformation temperature also affects the texture evolution during rolling of aluminum alloys [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…During the investigation of recrystallization in a two-phase Al-l.8%Cu alloy Engler (1995) found an influence of the initial grain size, i.e. the grain size before cold rolling, on the f'mal recrystallization texture.…”
Section: Nucleation Of Recrystallisation In Aluminium Alloysmentioning
confidence: 99%